The Influence of Knowledge Management on Employee Competencies at PT. Semen Indonesia Unit Tonasa - Muhammad, A Fadel; Joeliaty; Muizu, Wa Ode Zusnita (Economics and Business Journal (ECBIS), 2025)
This study examines the influence of knowledge management on employee competencies at PT. Semen Indonesia Unit Tonasa. Knowledge management, encompassing knowledge creation, storage, sharing, and application, plays a crucial role in enhancing employee knowledge, skills, and attitudes. Employing a quantitative approach, data were collected through structured questionnaires and analyzed using Structural Equation Modeling (SEM). The findings reveal a significant positive relationship between knowledge management and employee competencies, with a path coefficient of 0.512 and a t-statistic of 7.245. Among the dimensions, knowledge sharing emerged as the strongest contributor to competency development, fostering collaboration and collective learning. Employees reported significant improvements in technical expertise, problem-solving skills, and adaptability. However, challenges such as resistance to change, uneven participation, and resource constraints were identified as barriers to the full implementation of knowledge management initiatives. This study underscores the importance of structured knowledge management practices in developing a skilled and adaptable workforce. Practical recommendations include fostering a knowledge-sharing culture, addressing resistance to change, promoting inclusive participation, and investing in knowledge management systems. These insights are expected to contribute to the academic literature and provide actionable strategies for organizational development